Nanotherapeutic smart approaches for combating Alzheimer’s disease and overcoming existing obstacles: A novel eco-friendly green approach - Ahmed M. Almehdi; Doha H. Aboubaker; Rania Hamdy; Ali El-Keblawy (Toxicology Reports)
The scientific community has united to raise awareness of Alzheimer's disease (AD) as a critical condition for future generations because recent predictions indicate that it will become common among the elderly within a few years. Nevertheless, the intricacies of the disease's progression demand exhaustive investigations to unravel its potential mechanisms. Only then can clinicians develop more efficacious therapeutic strategies. Cognitive impairment caused by amyloid aggregation, the development of hyperphosphorylated neurofibrillary tangles, and a malfunctioning cholinergic system are the hallmarks of AD. Even after the disease has started, brain tissue integrity may degenerate. The physiological characteristics of the highly selective blood-brain barrier and the electrostatic charge of the nanoporous extracellular matrix have long placed restrictions on the treatment of brain disorders. A prospective revolution in drug delivery for the treatment of AD is the use of nanomedicine. It depends on enhancing the way that medications are distributed pharmacokinetically throughout the central nervous system. Several types of nanoparticles (Nps) are available thanks to nanotechnology, and these Nps could target the brain and have a long half-life with few systemic side effects and motor problems. With the latest technological developments, scientists are working to develop unique approaches for the treatment of AD. To evaluate the prospective uses of medicinal plants, their components, and different nanomedicine techniques, it was determined that this literature study was necessary. To provide an overview of the various challenges and approaches related to using nanoparticles (NPs) to combat Alzheimer's disease (AD), this introductory review article was developed.